Chikungunya Outbreak in Kedougou, Southeastern Senegal in 2009–2010. (2nd December 2017) - Sow, Abdourahmane; Faye, Oumar; Diallo, Mawlouth; Diallo, Diawo; Chen, Rubing; Faye, Ousmane; Diagne, Cheikh T; Guerbois, Mathilde; Weidmann, Manfred; Ndiaye, Youssoupha; Senghor, Cheikh Sadibou; Faye, Abdourahmane; et al.
Abstract: Background: In Senegal, Chikungunya virus (CHIKV), which is an emerging mosquito-borne alphavirus, circulates in a sylvatic and urban/domestic cycle and has caused sporadic human cases and epidemics since 1960s. However, the real impact of the CHIKV sylvatic cycle in humans and mechanisms underlying its emergence still remains unknown. Methodology: One thousand four hundred nine suspect cases of CHIKV infection, recruited from 5 health facilities located in Kedougou region, south-eastern Senegal, between May 2009 to March 2010, together with 866 serum samples collected from schoolchildren from 4 elementary schools in May and November 2009 from Kedougou were screened for anti-CHIKV immunoglobulin (Ig)M antibodies and, when appropriate, for viral nucleic acid by real-time polymerase chain reaction (rPCR) and virus isolation. In addition, mosquitoes collected in the same area from May 2009 to January 2010 were tested for CHIKV by rPCR and by virus isolation, and 116 monkeys sera collected from March 2010 to May 2010 were tested for anti-CHIKV IgM and neutralizing antibodies. Results: The main clinical manifestations of the CHIKV suspect cases were headache, myalgia, and arthralgia. Evidence for CHIKV infection was observed in 1.4% (20 of 1409) of patients among suspect cases. No significant difference was observed among age or sex groups. In addition, 25 (2.9%) students had evidence of CHIKV infection in November 2009. Chikungunya virus was detected in 42 pools of mosquitoes, mainly from Aedes furcifer, and 83% of monkeys sampled were seropositive. Conclusions: Our findings further documented that CHIKV is maintained in a sylvatic transmission cycle among monkeys and Aedes mosquitoes in Kedougou, and humans become infected by exposure to the virus in the forest.